Comparison of three port laparoscopic cholecystectomy with four port laparoscopic cholecystectomy (Bangladesh Journal of Medical Science, 2022)
Objective: Laparoscopic cholecystectomy, gold standard treatment for cholelithiasis, has traditionally been done using 4 ports. We compared four port procedure with newer 3-port cholecystectomy.Methods: Sixty patients were operated by equally dividing them into two groups and using two procedures mentioned in the objective.Results and Discussion: Assessment was carried out using parameters like operative time, cosmetic appearance and complications. Results were similar except operative time which was much less with 4-port procedure.Conclusion: It will require lot of training before three port laparoscopic cholecystectomy can become popular and beneficial compared to four-port procedure.Bangladesh Journal of Medical Science Vol. 21(1) 2022 Page : 151-157